Millennialization of Islamic Education Based on Neuroscience in the Third Generation University in Yogyakarta Indonesia - Suyadi Suyadi (P3M STAIN Kudus, 2019)
To date, Islamic Education in Indonesia is framed in traditional, conventional, and colonial paradigms. Despite the twentieth century’s urges to use interdisciplinary, multidisciplinary, and trans-disciplinary approaches, mono-disciplinary approach such as classic and medieval Islamic education, is still dominating. Researches in the three new methods have engaged neuroscience that results in innovative and reliable works, indicated by the achievement of Intellectual Property Rights with downstreaming potentials. The study aims to find a model for Islamic education that is based on neuroscience in the millennial era with the mentioned attainment. The research applied a qualitative model by Denzin and was located in the Magister Degree of Islamic Education of Universitas Ahmad Dahlan, Yogyakarta, in 2008. It involved six lecturers and thirty-one students. The data were collected through participatory observation, in-depth interview, and documentation.The research generates a neuroscience-based model for Islamic education in the millennial era through the development of research-based instruction. Further, the development allows the achievement of Intellectual Property Rights and downstreaming potentials. The model is the continuation of Islamic education modernization initiated by Muhammad Abduh and is relevant to the entrepreneurship of the millennial Muslim generation of the twenty-first century.